Door Security System Using e-KTP RFID Reading and Passive Infrared Sensor - Mohammad Adrian Faisal; Erwin Sitompul (President University, 2021)
A door, as a barrier to limit an access between two spaces, requires a security measure to ensure that only privileged people may pass. In this paper, a door security system using Radio Frequency Identification (RFID) and Passive Infrared (PIR) sensor is proposed. This security system utilizes an electric door lock and an e-KTP (Kartu Tanda Penduduk elektronik/ electronic Indonesian Identity Card) as the key. A sequence of numbers can be read from an e KTP by using an RFID reader. This sequence is unique, making an e-KTP suitable to be used as a key. Furthermore, the door security system is equipped with an alarm. A PIR is used to detect motion, and the alarm will sound if someone passes the door while the alarm is still in active state. The Arduino Mega microcontroller board is used to organize the whole system, consisting the aforementioned reader and sensor, along with two push-buttons, a buzzer, and a solenoid door lock. The system is realized into a prototype in the form of door miniature. A list of scenarios is played through to the system. Only authorized e-KTPs can be used to unlock the door and deactivate the alarm. The door security system successfully fulfils the objective to improve the security level of a door lock mechanism by utilizing an e-KTP as a unique RFID key and by featuring a PIR-integrated alarm.